Understanding the Role of Social Media Toward Satisfaction of Government in Indonesia - Sakti, Rangga Eka; Nainggolan, Bestian (JURNAL KOMUNIKASI INDONESIA, 2023)
Along with the massive internet penetration, the number of social media users in Indonesia increases significantly during this half decade. Besides being used as a medium to communicate, social media also plays a role as a source of information consumed by the public. This poses a dilemma. On the one hand, information becomes decentralized. But on the other hand, there is no verification mechanism for information in the social media space. The loss of this check and clarification process makes it easy for hoaxes, disinformation and misinformation to spread through social media, including those related to government performance as well as public policy issues. Previous studies have shown how social media impacted public’s perceptions toward the government across several countries both with positive and negative effects. Thus, this study aims to answer the relationship between the use of social media as a source of information of the public and their satisfaction with the government's performance through polls that were conducted 3 times during the period of 2021-2022 across Indonesia. The polls show various results which explain the different impacts of social media consumption toward people’s satisfaction with the government based on time frame and political partisanship.